ANALISIS KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI SAAT PANDEMI COVID-19 - Susanto, Fabiani Vanda; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700]DO - 10.24843/EEP.2022.v11.i09.p14, 2022)
Regional development is expected to be able to overcome ongoing problems such as reducing poverty levels, unemployment rates, very low education and other inequalities between regencies/cities so as to improve people's living standards. This study uses panel data with time series data for 5 years from 2017-2021 and cross section data for 9 districts/cities in Bali Province so that the total observations are 45 observation points. The data used is secondary data with data collection methods, namely non-participant observation. The data collected was then analyzed using panel data regression analysis techniques and multiple linear regression analysis. The results showed that the pandemic had a negative and significant effect on people's welfare, the district minimum wage had a positive and significant effect on people's welfare, and unemployment had no effect on people's welfare in the Regency/City of Bali Province. Keywords: Pandemic, District Minimum Wage, Unemployment, Community Welfare